Population genetics of bush-encroaching acacia mellifera at Pniel, Northern Cape Province, South Africa - Nxele, Beka Jeremia (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScConEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.